Besökares påverkan på Nordens Arks vargflock - Eliasson, Johanna (2005)
Zoo animals can be more or less disturbed by the presence of care takers as well as visitors. This may lead to stress and/or abnormal behaviour. The purpose with this study was to give a time budget of the behaviour of the captive wolves' (Canis lupus) and occurrence of behavioural disturbances and how this is affected of human visitors. For this purpose the wolves at Nordens Ark have been studied during off season as well as on season. The zoo Nordens Ark is an idealistic foundation which was founded in 1988 and is located at Åby säteri, 130 km north of Gothenburg. The park is open all year around and has about 140 000 visitors annually. The wolf pack consists of a family group of ten wolves, an alpha pair and their pups (3 males and 5 females). The wolves have three enclosures in connection with each other of 11 000, 2 500 and 1 000 m2. The observations were performed in connection with feeding and cleaning in the enclosure and continued for about two hours each time. A scan of the behaviour of the group was done every 30 seconds, two times daily for twenty days. Signs of abnormal behaviour were recorded continuously during the observation period. The study was performed during two periods corresponding off season (15 to 24 March) and on season (10 to 19 May) in 2004. During off season a larger proportion (25 %) of the wolves were active then during on season (13 %). The proportion of invisible wolves was 46 % off season and 56 % on season. The amount of inactive wolves were equivalent on season respective off season with 29 % and 31 %. Abnormal behaviour was observed at nine occasions off season while on season only three occasions were observed. Possible explanations for the higher proportion of active behaviour off season could be the fact that off season coincided with mating period and that one female wolf was pushed away from the pack and was euthanized during off season. This could also explain the higher proportion of abnormal behaviour off season. Another possible explanation could be that the number ...